Load modeling techniques in distribution networks: a review - Musa Mohammed; Abubakar Abdulkarim; Adamu Sa’idu Abubakar; Abdullahi Bala Kunya; Yusuf Jibril (Journal of Applied Materials and Technology, 2020)
Power system operation and control required models of generators, lines and loads to be accurately estimated, this is to enable operators make a reliable decision on the system. Generators and lines models are so far considered accurate, while load models are considered perplexing due to invention of new types of loads, distribution system are transforming from passive to active. Future distribution systems are desired to be smart and for a network to be smart the system as to be fully and accurately represented. Penetration of renewable energy and application of power electronic devices as well as participation of active customers in distribution systems make traditional methods of load modeling absolute. Accurate load modeling is required to address the new challenges evolving in the task of power system operation, control and stability studies. It is also an interest of power system researchers globally to realize Smart Networks (SNs), in which accurate load models are required. This work described a review of techniques and approaches for load modeling from traditional methods to the state of art in the area. In addition, gaps in the literature as well as research directions are also pointed out.